Postoperative Pyogenic Cervical Discovertebral Spondylitis - Sharma, Krishna (Nepal Journal of Neuroscience, 2016)
Postoperative cervical discovertebral spondylitis is an uncommon problem, especially if it occurs soon after another surgery somewhere else in the body. The diagnosis is late as the symptoms like neck pain, are initially ignored and may present later with features of unstable spine and neurological defi cits. Management is like for any other pygenic spondylitis and may need surgical debridement, decompression and fi xation. Overall prognosis is good with timely treatment. Since the neck problem occurs soon after a surgery elsewhere in the body, the previous surgery could be blamed for the present spondylitis. Thus this may add a medico-legal dimension to the problem. Nepal Journal of Neuroscience. Vol. 13, No. 2, 2016, Page: 81-87